Emerging Techniques for Nonlinear Optical Spectroscopy of Disordered and Highly Scattering Materials - Albert S. Reyna; Anderson M. Amaral; Cid B. de Araújo (Photonics, 2024)
Scattering materials have been of considerable research interest due to their unique optical properties that may enable applications throughout the area of disordered photonics, particularly in fields such as Random Lasers, nonlinear (NL) microscopy in biomedical research, and optical thermometry. However, the complex structures of these materials make traditional NL spectroscopic techniques unsuitable for studies, as the materials of interest can cause large multiple scattering of light in addition to presenting spatial heterogeneities. Fortunately, new techniques, such as the Scattered Light Imaging Method (SLIM), the Intensity Correlation scan (IC-scan), and the Reflection Intensity Correlation scan (RICO-scan), have recently emerged, providing researchers with more appropriate ways to study disordered and scattering NL materials. These techniques allow for a deeper characterization of the NL optical properties of highly scattering materials, which are essential for applications in photonics, optoelectronics, and biophotonics, for example. In this paper, we discuss these innovative techniques, which can offer insights into the properties of materials of great potential for disordered photonics.